The Use Of Force Majeure By Attorney Against Taxation Crime - Adnan Hamzah; Muhammad Djafar Saidi; Amir Ilyas (Fakultas Hukum Universitas Hang Tuah, 2018)
This study aimed to see the effectiveness of using force majeure along with the challenges the attorney might encounter against taxation crime. It was a normative study with statute and case approaches. The study was conducted in High Prosecutor General office in Makassar and Directorate General of Tax South Sulawesi. The result showed that the force majeure by attorney against taxation crime might be applied in the form of detention to complete particular documents and conduct an additional investigation before filing the case to the court. The challenges in implementing the force majeure by attorney against taxation crime might come from legal and non-legal factors. The former involved confusing phrase of ‘investigation termination’ by attorney and the light different view on state financial losses between under Corruption Law and under General Act of Taxation, and the later involved the professionalism of attorney and information transparency.